Development of controller for an underactuated autonomous underwater vehicle (AUV) - Mat-Noh, Maziyah; Zain, Zainah Md; Abd Ghani, N. M.; Abdul Wahab, Yasmin; Razali, Akhtar Razul (2019)
The autonomous underwater glider (AUG) demonstrates highly nonlinear and complexity in its dynamic model and also coupled with external underwater environment and disturbance. With limited actuators, the only option that AUG has in facing such environment and disturbances is by using strategies of control algorithm. For this reason, the main objective of this research is to formulate the control law that has the capability in facing the external disturbances and uncertainties due its hydrodynamics coefficients. As a result, a robust and reliable has been designed using back-stepping super twisting sliding mode control algorithm (BSTSMC) for nonlinear model of longitudinal plane of an AUG. The BSTSMC was tested for external disturbance and parameter variations. The BSTSMC has been benchmarked its performances with other sliding mode control (SMC) strategies to evaluate the chattering suppression of the controllers. The BSTSMC was benchmarked with super twisting SMC (STSMC) and back-stepping SMC. The simulation results have shown that the proposed controller provides the smallest chattering about more than 1000 times smaller than STSMC, more than 100 times smaller than back-stepping SMC in nominal, disturbance and parameter variation cases respectively. The steady error of the proposed controller also gives the smallest steady state error of four times smaller than STSMC and back-stepping SMC in all cases for pitching angle and 100 times smaller than STSMC and back-stepping for excess mass. The proposed controller is a new chattering suppression method which provides the smallest steady state error and chattering has been also suppressed in all cases.